A mixed integer programming approach to a square fully fuzzy linear equation - Ahlatcioglu, Mehmet; Albayrak, Inci; Kocken, Hale Gonce; Ozkok, Beyza Ahlatcioglu (IOS PRESS, 2016)
In this paper, a new method is proposed to find the feasible (strong) fuzzy solution of a square (n x n) fully fuzzy linear equation system (FFLS) with triangular fuzzy numbers. The main purpose of the proposed method is to remove all the sign restrictions on the parameters and variables. Our method, which is based on the multiplication of two arbitrary triangular fuzzy numbers, converts the FFLS to a mixed integer programming problem. The method is illustrated with numerical examples.
Keywords: Linear equation system; fuzzy number; fuzzy decision making; mixed integer programming; SYSTEM; DECOMPOSITION; Computer Science